CFD prediction of the effect of heel and trim on the resistance of an Olympic dinghy - Peter, Jeremy; Lindstrand Levin, Rickard (My University, 2014)
Sailing the Laser dinghy will be an Olympic discipline at the 2016 summer Olympic Games in Rio. The Olympic motto reads: Higher - faster - stronger. For competitive sailing nowadays this means using scientific measures to improve boat speed and distance made good. This thesis is a part of Chlamers' sports technology effort which aims at improving of developing certain sports. This thesis in particular is undertaken in the aim at gaining insights on the parameters that affect the hydrodynamic resistance of the hull of the Laser dinghy. Gaining knowledge in how to minimize resistance will in turn provide the sailors with instructions of how to sail better. Investigations of this kind have never been done before on any dinghy, this increases the potential for an advantage for the Swedish sailors. As the Laser is a strict one-design class no means of design change is possible. The overall goal of the sports project is to improve the performance of the sailors. The purpose of this thesis is to see if the minima in resistance can be predicted to occur at the same angles of heel and trim for: bare hull towing tank tests, bare hull simulations and appendage and leeway simulations. If this is the case the appendages and the leeway can be rejected from future investigations of this kind. This would be beneficial as they impose further complexity to the simulations. To get direct instructions of how to sail according to the results obtain in this thesis, more work than presented here is needed. Towing tank tests performed at SSPA in Gothenborg are the input and the starting point of this thesis. The test were performed for variations of speed and heel and trim angles, for a bare hull. In the first phase of the project, a verification and validation, V&V, analysis is achieved to gain confidence in the CFD simulations run in the Shipflow software. The verification is done to display and effect of the grid on the outcome of the simulation, the procedure is called grid dependence study. The V&V was done for one test case with 4 kts boat speed. The second part of the thesis work was to run simulations with similar conditions as in the towing tank and then validate the results against the towing tank test data. This was done for heel and trim variations at 3 and 4 kts. The third part was to include the effect of appendages and the leeway to the simulations, and then see if the resistance minima occurred for the same angles of heel and trim. The results from the V&V study showed that the numerical method predicted a too low resistance. Possible sources of error were identified and systematically investigated but the major source of error was not found. However some possibilities are explained and ruled out for future reference. Furthermore, not all simulations for the investigation were finished or did not provide satisfactory and reliable results. Having an incomplete set of results, conclusions on the angles of heel and trim leading to minimal resistance could not be made. A discussion about what needs to be done in order to reach those objectives, and what could improve a study like this one in the future, is given in the end of this report.
Keywords: Oceanografi, hydrologi, vattenresurser; Farkostteknik; Oceanography, Hydrology, Water Resources; Vehicle Engineering